GnRH agonist and letrozole in women with recurrent implantation failure - Sharma, Nidhi (Annals of Translational Medicine, 2019)
The manuscript addresses a very intriguing question of cause of recurrent implantation failure (RIF). RIF for the purpose of research is adequately defined and stated in the manuscript. However, the definition of RIF in current literature is unfortunately not yet standardised (1). The definition states that absence of “implantation” after two or three consecutive assisted reproductive technology (ART) cycles (both fresh and frozen embryo cycles) with total transfer of ≥4 cleavage stage embryos or >2–3 blastocysts of “optimum quality”.